The short-term effects of topsoil inversion tillage on soil carbon storage, New Zealand - Dijkstra, Jorn (Student Undergraduate Research E-journal!, 2019)
There is an interest in the potential of increasing soil organic carbon (SOC) stocks in soils, as this increase may contribute to mitigate the impact of climate change. Pastoral soils as those of New Zealand accumulate large amounts of SOC in the topsoil because of C input from grass is concentrated in the root zone. Deep ploughing or topsoil inversion tillage at pasture renewal (TIT-renewal) has been proposed as a technique to accelerate SOC storage in pastoral soils. This study focuses on short-term effects of contrasted cultivation (tillage) practices at pasture renewal, shallow tillage and TIT, in soil C stocks. Six months after cultivation, the effect of deep ploughing was to redistribute C in the profile and no C changes were detected till a depth of 40 cm, when compared to shallow tillage.